2017
DOI: 10.1016/j.est.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Empirical equation to estimate viscosity of paraffin

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.0 de Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…Viscosity results measured for distilled water showed average deviations lower than 1.9% with previous literature[40]. A good agreement was also found between the value of 3.32 mPa•s determined in this work at 303.15 K for bulk-RT21HC and the previous data of 3.16 mPa•s reported at the same temperature for bulk-RT21 (another commercial paraffinic PCM with similar melting point) by Ferrer et al[41]. Shear Viscosity-Shear Rate Flow CurvesFigure 2shows the shear viscosity dependence on shear rate obtained at 278.15 and 303.15 K for water, bulk-RT21HC and four nano-emulsions.…”
supporting
confidence: 91%
“…Viscosity results measured for distilled water showed average deviations lower than 1.9% with previous literature[40]. A good agreement was also found between the value of 3.32 mPa•s determined in this work at 303.15 K for bulk-RT21HC and the previous data of 3.16 mPa•s reported at the same temperature for bulk-RT21 (another commercial paraffinic PCM with similar melting point) by Ferrer et al[41]. Shear Viscosity-Shear Rate Flow CurvesFigure 2shows the shear viscosity dependence on shear rate obtained at 278.15 and 303.15 K for water, bulk-RT21HC and four nano-emulsions.…”
supporting
confidence: 91%
“…In addition, these results are tied to an analogous study conducted by the authors [28] corrective parameter, as the influence that the carboxylic group has in the melting temperature is different and more important than the carbon atoms difference in paraffin chains. This accordance to study [31] corroborates the suitability of the equation found in this study and indicates that polynomial 3 models are useful equations to predict viscosity of organic PCM.…”
Section: Viscositysupporting
confidence: 89%
“…Previous studies measured the viscosity of some of these PCMs at lower temperatures, and Ferrer et al 41 even derived an empirical equation to calculate the viscosity of organic PCM (Equation () and Equation ()): μ()T[]italicPa·s=()3.66×108·T3+6.14×106·T24.35×104·T+1.41×102·c c=0.001·Tm20.0215·Tm+0.5815 …”
Section: Resultsmentioning
confidence: 99%